Computer‐Guided Surgery Using Human Allogenic Bone Ring With Simultaneous Implant Placement: A Case Report. Issue 1 (14th October 2019) - Simpson, Kerri Thomas; Bryington, Matthew; Agusto, Michele; Harper, Matthew; Salman, Arif; Schincaglia, Gian Pietro
Abstract : Introduction: The allogenic bone ring technique allows for horizontal and vertical bone augmentation with simultaneous implant placement in severely compromised sites. The aim of this report is to present a modified protocol for simultaneous placement of implant and allogenic bone ring graft using a computer‐guided surgery technique. Case Presentation: Patient's chief complaint was to replace a missing lateral incisor. The implant site presented both vertical and horizontal tissue deficiencies. Study models and wax‐ups were digitally scanned to stl files and merged with the existing CBCT data in the implant planning software. A 3D representation of an allogenic bone ring was developed, and two digitally designed guides were created: a 5 mm sleeve guide for the implant site and a 7 mm sleeve guide for the allogenic bone ring trephine. Both the implant site and the allogenic bone ring recipient site were prepared using the computer‐generated guides. Once the ring was adapted into the recipient site, the implant was inserted through the allogenic bone ring. The healing was monitored and the implant was restored at 12 months. The accuracy of implant placement was measured and the difference in the final positioning was as follows: 0.6 mm at entry point, 0.55 mm vertical displacement, 1.94 mm at the apex, and angle discrepancy 6.1°. Conclusion: The use of computer‐guided technology for planning and placement of an allograft bone block with simultaneous implant insertion allows for a prosthetically driven team approach to compromised site grafting in addition to improving precision and accuracy when compared with non‐guided techniques.